Implantation of a Thoracic Spinal Cord Stimulator Paddle Electrode and Generator Under General Anesthesia With Intraoperative Neuromonitoring: 2-Dimensional Operative Video. Issue 6 (5th October 2018) - Stone, Lauren E; Falowski, Steven M
Abstract: Spinal cord stimulation is a well-established and effective therapy in the treatment of pain. Proper patient selection and accurate lead placement are paramount in its success. Placement is a multifaceted process requiring proper paddle placement, a well thought out generator placement and appropriate means to limit complications and enhance success. Several intraoperative techniques maximize outcomes, including removal of the superior portion of the inferior level's spinous process for paddle access into the epidural space, generator pocket placement in a location that limits patient discomfort, a strain relief loop at the thoracic incision to prevent lead fractures and allow for full spinal flexibility, generator placement parallel to the body and secured in the pocket to prevent unwanted movement, and intraoperative neuromonitoring for patient comfort and more accurate lead placement compared to X-ray alone or awake placement. This case demonstrates these key elements of intraoperative technique in a candidate with the most common indication for spinal cord stimulator placement–postlaminectomy syndrome–underscoring the ease and viability of this procedure in the appropriate patient population in a means that reduces future complications and adverse events while maximizing success.  Full patient consent for video-recording and subsequent use for research purposes was attained. All patient identifiers have been removed for the purpose of patient confidentiality.